Motivational Factors to Become EFL Teachers: A Phenomenology Study on Fresh Graduates - Arie Arisandi; Rizka Vanissa (Journal of English Language Teaching and Literature)
Being a teacher is a favorite goal lately, in contrary to what happened in the past. This current study aimed at (1) finding out factors that encourage fresh graduates to become EFL teachers, and (2) elaborating the meaning of being EFL teachers. The subjects of this qualitative study were four young EFL teachers who were fresh graduates and became teachers less than a year at different secondary schools in Makassar. To collect data, researchers used in-depth interview technique. Data were analyzed using Interpretative Phenomenological Analysis (IPA) technique. The results of this study found that the motivating factors of being EFL teachers were to help students reach or realize their future, to get life lessons, as the call of the soul, and to enjoy comfort. The meaning of being an EFL teacher found through this research were as a job or profession, as an expression of belief in religion, and the way to feel as parents for students.